Outcome of low dose daily versus standard alternate day prednisolone for frequent relapse nephrotic syndrome in children - Billah, M. Masum; Afrin, Tanjila; Shamsad, Sadia; Khatun, Anjuman Ara; Uddin, M. Reaz; Khan, M. Anwar Hossain; Ul Alam, A. B. M. Mahbub (International Journal of Contemporary Pediatrics, 2026)
Background: Nephrotic syndrome is a common chronic glomerular disorder in children, with frequent relapses causing significant clinical and psychosocial burden. Prednisolone remains the cornerstone of therapy, typically administered on an alternate-day schedule for maintenance. However, low daily-dose regimens may improve relapse control with fewer adverse effects, particularly in resource-limited settings. Methods: This quasi-experimental study included 72 children aged 2-12 years with FRNS treated at the National Institute of Kidney Diseases and Urology, Dhaka, between August 2022 and August 2024. Participants received either daily low-dose prednisolone (0.2 mg/kg; Group A, n=31) or alternate-day prednisolone (0.5 mg/kg; Group B, n=32) for six months. Clinical features, anthropometric measurements, laboratory findings, relapse frequency, and steroid-related adverse effects were assessed at baseline, 3 months, and 6 months. Data were analyzed using independent T-tests and chi-square tests, with p<0.05 considered significant. Results: Baseline characteristics were comparable. At 6 months, oedema, ascites, and significant proteinuria were more frequent in Group B (70% vs. 41.4%, p=0.027). Group A had a lower cumulative prednisolone dose (60.57±24.79 mg/kg vs. 76.01±14.21 mg/kg, p=0.005), fewer Cushingoid features (3.4% vs. 20%, p=0.049), better BMI preservation, lower relapse rates (41.4% vs. 70%, p=0.027), and higher remission rates (58.6% vs. 30%, p=0.027). Conclusions: Daily low-dose prednisolone appears more effective and safer than the standard alternate-day regimen in maintaining remission in children with FRNS.